Exposure to Carbon Nanotubes Leads to Changes in the Cellular Biomechanics. Issue 7 (18th January 2013) - Dong, Chenbo; Kashon, Michael L.; Lowry, David; Dordick, Jonathan S.; Reynolds, Steven H.; Rojanasakul, Yon; Sargent, Linda M.; Dinu, Cerasela Zoica
<x xml:space="preserve">Abstract</x> Exposure to carbon nanotubes induces significant changes in cellular biomechanics. Using nanoindentation, it is observed that the exposed cells have significantly higher stiffness when compared to controls, especially at the nuclear region, and significant increases in surface area. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>